2014
DOI: 10.1016/j.jval.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A Program of Methodological Research to Arrive at the New International EQ-5D-5L Valuation Protocol

Abstract: The EuroQol Group has developed a standard protocol, with accompanying digital aid and interviewer training materials, that can be used to create value sets for the EQ-5D-5L questionnaire. The use of a well-described, consistent protocol across all countries enhances the comparability of value sets between countries, and allows the exploration of the influence of cultural and other factors on health state values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
422
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(432 citation statements)
references
References 29 publications
3
422
0
7
Order By: Relevance
“…The purpose of the valuation questionnaire was to obtain numeric "values" reflecting the strength of respondents' preferences for different EQ-5D-5L health states, as necessary to facilitate the use of EQ-5D-5L data in economic evaluation. This comprised a series of time trade-off and discrete choice experiment tasks (following an adapted version of the EuroQol Group protocol for valuing EQ-5D-5L health states [25]). A computer-based tool was used to administer the valuation tasks and to capture the response data.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…The purpose of the valuation questionnaire was to obtain numeric "values" reflecting the strength of respondents' preferences for different EQ-5D-5L health states, as necessary to facilitate the use of EQ-5D-5L data in economic evaluation. This comprised a series of time trade-off and discrete choice experiment tasks (following an adapted version of the EuroQol Group protocol for valuing EQ-5D-5L health states [25]). A computer-based tool was used to administer the valuation tasks and to capture the response data.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Our study found a difference between both indices in the negative extreme of the theoretical range (-0.28 and -0.53). This difference is explained by the method used for the elicitation of the societal preference values to derive the value set: time tradeoff in French general population for the 3L version [46], and the composite method of time trade-off with discrete choice experiments in the UK general population for the new 5L version [19,25]. Our findings show that the mean EQ-5D-5L indices obtained with both value sets is quite similar (0.88 and 0.83), supporting that the 3L-5L crosswalk is a good interim solution to calculate the EQ-5D-5L…”
Section: Comparison With Prior Studies Evaluating the Eq-5d In Patienmentioning
confidence: 99%
“…To improve its sensitivity, the EuroQol Group developed a new EQ-5D version, by increasing the number of responses from 3 to 5 levels, known as EQ-5D-5L with 3,125 health states (i.e. 5 5 ) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Na verdade, antevê-se que a utilização da DCE continue a crescer particularmente em estudos na área da saúde. A integração recente desta técnica no protocolo de valoração do EQ-5D-5L descrito em Oppe et al (2014), será um fator determinante na sua crescente utilização.…”
Section: Conclusãounclassified